Plano museológico: um marco na gestão de museus à luz da gestão da informação e do conhecimento - Claudia Maria Alves Vilhena (2017)
Museums have an important role in society, within these institutions are developed various activities, so that our musealized cultural assets are preserved and communicated to the public, leading to an efficient management of their functions. To this end, the basic functions of museums need theoretical support and methodological procedures appropriate to the challenges imposed on them. Today's society increasingly demands of the museum a qualified performance of its mission. Its creation and permanence must occur as a planned process, always reevaluated and in connection with the scientific field of the area, Museology. The museological plan, as the result of this process, is a museological, informational and institutionalized document, which contributes to the managers in the decision-making. This is a methodological procedure to support museum management. The research seeks to answer to what extent the museological plan contributes to museological management. This work intends to contribute to the museological institutions regarding the applicability of the institutional museological plan, demonstrating that this, when elaborated in a participatory way, that is, in the use of information as a strategic and determinant resource, through the sharing of information between the staff of the institution, becomes an important document for the museum. This is an exploratory qualitative research whose method for collecting data was carried out through the application of a semi-structured questionnaire sent by direct mail to four museums: a museum directly administered by the Brazilian Institute of Museums; A museum belonging to the Superintendence of Museums in Minas Gerais; A museum belonging to the Municipal Foundation of Culture of Belo Horizonte and a private museum, followed by documentary analysis of the museological plan of each institution. The result obtained demonstrated that the preparation of the museological plan requires meetings and discussions with the participation of all sectors of the institution to jointly discuss the museological achievement and thus achieve the expected efficiency in the management of the museum.